The Role of Islamic Religious Education Teachers in Developing Student Personality - Megawati Abbas; Aryandi Sudika (International Journal on Advanced Science, Education, and Religion, 2023)
This study aims to develop the personality of students in accordance with the goals of Islamic religious education, namely creating human beings with Muslim personalities. This type of research is descriptive-qualitative using an interdisciplinary approach, namely pedagogical, psychological and religious and philosophical. The research location is focused onAl-Islam Middle Schoo Fort Tellue Kec. Bone District Amali. This research found several important points including; 1). Educators and education staff at Al-Islam Middle School Benteng Tellue, Kec. Amali Bone Regency accumulatively totals 11 people consisting of permanent teachers and non-permanent teachers, as well as staff or employees and the majority have a Bachelor's education qualification (S1) and there is 1 person who has a master's qualification (S2) from various fields of science; 2). The efforts of Islamic religious education teachers in developing the personality of students through education, guidance and direction in accordance with Islamic values. Providing exemplary as an effort to accustom students to good behavior; 3). Supporting factors, in addition to the qualifications of PAI teachers meeting the standards and the subjects taught in accordance with their scientific disciplines and infrastructure are supporting factors in developing the personality of students; inhibiting factors such as, lack of study hours for religious lessons, student awareness of the importance of Islamic religious education, environmental/social influences and lack of attention and cooperation from parents of students. Keywords: The Role of Islamic Religious Education Teachers, Student Personality Development